Implementation of Problem Based Learning Component for Open-Ended Engineering Laboratory: Early Comparison on Students’ Performance - Rudiyanto, Philman Jong; Khairul Fikri, bin Tamrin (Majmuah Enterprise, 2018)
Problem based learning has been adopted worldwide in several disciplines of education particularly in medicine. The opportunity for implementation of problem based learning component was observed with the implementation of open-ended laboratory in engineering education. Achievements of students in two cohorts were compared to assess the effectiveness of the problem based learning component implementation component in Engineering Laboratory 4. The results shows promising improvement in students’ achievements.